Evaluación de la eficacia de fungicidas para el control de Pyricularia grisea y Bipolaris oryzae en el cultivo de arroz (Oryza sativa), variedad Capirona en el Bajo Mayo, San Martín - Vásquez Lozano, Laith (2008)
The title of our investigation is: “Evaluation of the effectiveness of the fungicides to control the Pyricularia grisea and Bipolaris oryzae in rice cultivations (Oryza sativa) in the Bajo Mayo region, in San Martín, PERÚ”; Our objectives are: evaluate the incidence and severity of the illnesses of rice cultivations caused by the funguses called: Pyricularia grisea and Bipolaris oryzae, in order to determine the effect of the control of the new fungi combination comparing with the traditional fungicides and evaluate the performance and the cost of production in order to determine the effectiveness of the treatment. Our investigation took place in the “Fundo Cacatachi” Farm of the National University of San Martín – Tarapoto, PERÚ, and located, approximately, 8 Km far from Tarapoto city, to the left side of the “Fernando Belaunde Terry Road”, in a 5 month period. We used the Complete Block Random Design, with 9 treatments (fungicides) and 4 repetitions, the fungicides we used were: Stratego 250 EC (Propiconazole & Trifloxystrobin, (dose: 0,50 ; 0,75 y 1 l/ha); Flint 50 WG (Trifloxystrobin, (dose: 0,10 y 0,20 l/ha); Protexin 500 SC (carbendazim); Fuji one 400 EC (Isoprotiolene) y Silvacur Combi 300 EC (Tebuconazole & Triadimenol). The results obtained indicate that the fungicide Trifloxystrobin, dose: 0,20 l/ha, reduced significantly the pathogenics: Pyricularia grisea, Bipolaris oryzae and Rhizoctonia solani having an influence over the performance and benefits and cost. To fight illnesses of the leaves caused by Pyricularia grisea, Bipolaris oryzae y Rhizoctonia solani, we recommend the application of propiconazole & Tricloxystrobin, (dose 0,75 l/ha.)